A LITERATURE REVIEW ON GENITAL SELF IMAGE IN WOMEN AND AFFECTING FACTORS - Ayşe Nur Yılmaz (Rojan GÜMÜŞ, 2020)
The genital self-image, which is an important factor for women's health, has been defined as the self-attitude and the following emotion arising directly or indirectly from special interactions and experiences involving the genital organs. Women's beliefs and feelings about their genital organs are expressed as a sensitive subject because they are seen as secret and taboo. But nowadays many women find the appearance of their genital organs very important and are more interested in appearance. Although both women and men report negative genital self-images, research has shown that men tend to have a more positive genital self-image than women. Genital self image; body image, organ loss, sexual functions, genital hygiene practices, vaginal infections, culture, obesity, developmental periods and media. When we look at the literature, body image studies mostly focused on women's attitudes towards beauty, weight, and skin color, leaving the issue of genital self-image in the background. In fact, genital self-image plays an important role in the development of sexual health and body image. Recently, it has been found that women have an increasing desire to undergo genital cosmetic / plastic surgery operations and change the appearance and functions of their vulva and vagina due to their negative views on their genital self-image. It is important to examine all the factors that affect the genital self-image, which is of great importance for women's health, and to provide the necessary care by taking a holistic approach in terms of body perception and sexuality. Nurses / midwives should adopt approaches to increase the body and genital image of women and to increase the quality of life of individuals. Nurses / Midwives are healthcare professionals in the most appropriate position to provide the necessary support in developing a new genital self-image and positive lifestyle.